Climate and vegetation structure determine plant diversity in Quercus ilex woodlands along an aridity and human-use gradient in Northern Algeria - Ihaddaden, Akli; Velázquez, Eduardo; Rey-Benayas, José María; Kadi-Hanifi, Halima (Flora - Morphology, Distribution, Functional Ecology of Plants)
Abstract We studied the influence of environmental factors relating to climate, soil and vegetation cover on total species richness, species richness of different life-forms and species composition of plant communities occurring in Quercus ilex woodlands, across a 450-km long transect in Northern Algeria constituting a gradient of aridity and human use. We sampled vegetation and collected environmental data in 81 10 m × 10 m plots in five zones representing the largest Q. ilex woodlands throughout the study area, analysing them within an a priori hypothesis framework with the use of Path Analysis. Changes in plant diversity were mainly influenced by environmental factors related to precipitation and temperature regimes, as well as by total plant cover. In particular, changes in species composition were determined by factors associated with the temperature regime through their influence on both woody and annual herbaceous plant richness, and by factors related to the precipitation regime through their influence on perennial herbaceous plant richness, likely due to the differential tolerances of these functional groups to cold and water stress. Our results emphasize the importance of differences in environmental adaptability of the most important life-forms with regard to explaining compositional change (beta diversity) along aridity gradients, and the mediator role of total plant cover in relation to the effects of soil conditions on plant diversity.
Keywords: Path analysis; Plant life-forms; Precipitation regime; Species composition; Species richness; Temperature regime; Total plant cover